Pinch-based targeting for production planning for small and medium enterprise - Lim, Song Hok (2015)
Pinch analysis techniques have been widely used as systematic design tools in the chemical process industry over the past decades. However, there has been very limited work on the use of pinch analysis in the area of production planning. Some of the common problems encountered by Malaysian small and medium enterprises (SMEs) are fluctuation of demand and supply of goods, inadequate warehouse, machine allocation problem, and the lack of factory space. With the application of systematic production planning techniques based on pinch analysis, these problems can now be resolved. The research objective of this dissertation is to develop novel graphical tools for production planning for the SMEs. In this dissertation, new pinch targeting techniques known as production planning pinch diagram and production planning grand composite curve (PPGCC) are presented to assist production planning in the SMEs. The research methodology adopted was from similar graphical tools utilized for the recovery of energy, material resources, carbon capture and storage, production supply chain and human resource planning in the chemical process industry. The targeting techniques are graphical in nature where pinch point that acts as production bottleneck can be identified and opportunities for operational changes can be explored easily. Four illustrative examples and four industrial case studies were done to demonstrate how pinch analysis could be used to solve the various production planning problems faced by the SMEs. The case studies show that pinch analysis is practical for the manufacturing industries and provides tangible benefits such as cost savings from reduction of outsourcing and lead time, as well as better cash flow management. The developed methodology in this dissertation can also be extended to a broad range of applications, such as large scale manufacturing, logistics, agriculture, aquaculture, livestock, infrastructure development, forestry, medical, automotive, immigration, town planning and construction.